Exploring Higher-Lying Electronic States of a Molecular Switch by Coherent Triggered-Exchange 2D Electronic Spectroscopy - Nuernberger P.; Buback J.; Kullmann M.; Ruetzel S.; Brixner T. (EPJ Web of Conferences, 2013)
We use pump-repump-probe transient absorption spectroscopy to investigate the role of higher-lying electronic states in the photochemistry of a molecular switch. Moreover, replacing the pump pulse by a pulse-shaper-generated phase-stable double pulse, triggered-exchange two-dimensional (TE2D) electronic spectroscopy is established in the visible regime.